Pengenalan Akuntansi Aset Tetap Berwujud Stright Line Method - Isbul Waton; Nelsi Adryana; Ratih Kusumastuti (Trending: Jurnal Manajemen dan Ekonomi, 2023)
Tangible fixed assets are one of the important factors that determine the smooth running of a company, especially industrial companies. Without fixed assets, the industry cannot carry out its main activities. Talking about fixed assets cannot be separated from acquisition costs, depreciation and accumulated depreciation. Capital assets wear out occasionally due to normal use. This normal wear and tear must be amortized or financed over the life of the asset. It is not uncommon for unexpected damage to property, plant and equipment to occur as a result of natural disasters. such as floods and fires. Regardless of the cause for the reduced useful life of a tangible capital asset, either due to normal use, being sold because it is deemed no longer effective, or damaged due to a natural disaster, all must be properly accounted for. With accurate accounting records, every company will get accurate information about fixed assets